Hubungan Body Image Dan Imaginary Audience Terhadap Kepercayaan Diri Pada Remaja SMK Telkom Lampung - Diah Sabrina Sonya Pambudi; Octa Reni Setiawati; Prida Harkina (Nathiqiyyah, 2026)
Adolescence is characterized by physical and social changes that impact self-confidence, influenced by body image and the imaginary audience. This study aims to determine the relationship between these two variables and the self-confidence of adolescents attending Telkom Vocational High School in Lampung. Using a quantitative method with a correlational design, this study involved 223 students (57.8% female, mostly aged 16) selected through accidental sampling. Data were collected using a valid and reliable Likert scale (self-confidence, body image, imaginary audience) and analyzed using multiple linear regression using SPSS 26. The results showed an R² of 0.796, meaning that body image (32.83%) and the imaginary audience (46.68%) explained 79.6% of the variation in self-confidence. The majority of respondents had low self-confidence (65%), moderate-high body image (93.3%), and low imaginary audience (70.9%). The imaginary audience had a dominant influence. In conclusion, body image and the imaginary audience were significantly related to self-confidence, highlighting the need for interventions such as counseling to increase self-acceptance and social awareness to support the development of self-confidence in vocational high school adolescents. Keywords: Body Image, Imaginary Audience, Self-Confidence, Teenagers